Canopy Functions of R. maritima and Z. marina in the Chesapeake Bay - French, Emily; Moore, Kenneth (Frontiers in Marine Science, 2018)
Shoots in seagrass beds form canopies: structurally complex habitats that provide refuge for fauna and trap sediment particles by dampening water movement. Unfortunately, seagrasses are faced with continuing negative impacts to survival, including climate change and poor water quality. In areas where several seagrass species coexist, changing conditions may influence composition of beds so one species is favored over another. Two species found worldwide, Zostera marina and Ruppia maritima, are undergoing this shift: as Z. marina dies back, in some locations it is replaced by R. maritima, a smaller-form seagrass with shorter, thinner shoots. This process is occurring in Virginia, USA in the southern Chesapeake Bay, at intermediate depths where the species co-occur. Although changes in seagrass species abundance have previously been documented, few studies have measured the resulting effects on ecosystem functioning. We evaluated three sites to determine whether canopies of the two species displayed similar small epifaunal invertebrate animal assemblages and sediment properties, and found that Z. marina beds exhibited a greater amount of fine surface sediment than those of R. maritima, but found no effect of seagrass species on invertebrate assemblages. Epifaunal invertebrates were however more numerous and speciose with greater biomass, and more abundant with greater shoot density. This study provides baseline information from one summer for areas where the two seagrass species coexist. Although more research is needed, this study suggests in mixed beds, decline of Z. marina could result in coarsening of sediment, but dense R. maritima canopies could harbor similar small invertebrate assemblages.